Gender dalam Perspektif Islam dan Ilmu Pendidikan - Hadi, Mochammad Sabiq Al; Nazila, Intan Putri (ALSYS, 2025)
This study is grounded in the limited comprehensive research that integrates Islamic theological perspectives with modern educational theory in addressing gender education, despite the fact that gender inequality and stereotypes in Islamic educational institutions significantly influence character formation, social justice, and students' learning opportunities. The aim of this research is to formulate a conceptual framework for gender education rooted in Islamic values of justice such as ‘adalah (justice) and musawah (equality), integrated with critical and constructivist pedagogical approaches. A qualitative method with a library research approach was employed, utilizing primary sources such as the Qur’an and Hadith, as well as secondary references including classical and contemporary tafsir, literature on Islamic gender thought, academic journals, and educational theory. Data analysis was conducted through thematic content analysis to identify key patterns in the texts. The findings reveal that Islam, in its essence, rejects gender subordination and emphasizes justice and equitable partnership between men and women. However, in practice, Islamic education remains influenced by patriarchal cultures and gender-biased normative interpretations. Modern educational theory, particularly critical pedagogy offers a methodological framework to reconstruct Islamic understandings toward more just and transformative outcomes. The study concludes that synthesizing Islamic gender justice principles with critical pedagogy is essential for building an Islamic educational system responsive to gender equity. The implications include the development of justice-based curricula, gender-sensitive teacher training, and the expansion of inclusive education research agendas in Islamic schools.